Factors affecting the young Vietnamese customer's willingness to participate in fashion - Nguyễn, Thị Thoa (2020)
To reduce the damaging effects of fast fashion, fashion rental is becoming the global trend and potential business model which brings many benefits to both customers and providers. Therefore, the studies on this field are very necessary and meaningful, which will receive a lot of attention. Combining the Theory of Planned Behavior (TPB) and Technology Acceptance Model (TAM), this study investigates the determinants of young Vietnamese consumers‘ intention to using online fashion rental service. Specifically, the research focuses on a group of subjects who were born after 1995, called generation Z. Based on the out standing characteristics of this group, the paper offers new hypotheses compared to other prior studies in the same field. In particular, it specifies the effects of two variables:electronic- word of mouth (E-WOM) credibility and in fluencer marketing on subjective norm.